Analisis Kesulitan Guru Dalam Mengembangkan Media Pembelajaran Di MIS Mardliatul Islamiyah - Falih Daffa; Irlyanova Sabina; Nita Afriani Siregar; Nurhafizah; Safran (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
This research aims to determine teachers' difficulties in developing learning media at MIS Mardiatul Islamiyah. The research method used is qualitative descriptive research. Data collection in this research was carried out using observation and interview methods. The research results showed that teachers' difficulties in developing learning media at MIS Mardliatul Islamiyah were 1) teachers did not have much time, 2) costs were quite expensive, 3) difficulty operating technology, 4) age factor and 5) inadequate facilities and infrastructure. Several ways to overcome this problem are by utilizing available media, using simple learning media, collaborating with teachers, holding training and attending seminars and workshops.